ASSISTANCE IN CREATING BUSINESS LICENSES AT KANTOR NOTARIS VIVIN, S.H., M.KN. WITH THE USAGE OF ONLINE SINGLE SUBMISSION - RISK BASED APPROACH (OSS-RBA) SYSTEM - Shane Edwin; David Tan (ConCEPt - Conference on Community Engagement Project, 2022)
Indonesia is a country with very rich natural resources so this causes investors and business actors to be interested in investing in Indonesia, but to support economic development and current technological developments, the government creates a system, namely the Online Single Submission System - Risk Based Approach. based on Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing, which was previously the Online Single Submission system with the aim of cutting lengthy, time-consuming bureaucracy and providing the best service to the community. Notary Office Vivin, S.H., M.Kn is a partner in the Community Service Program with the aim of knowing how the processes of making business licenses are through the Online Single Submission – Risk Based Approach system.